Macroeconomic Instability, Migration, and the Option Value of Education - Eliakim Katz; Hillel Rapoport (Bar-Ilan University, Department of Economics, 2001)
We explore the relation between variability in the rate of return to human capital and investment in education in the context of migration. Specifically, we show that if migration is a possibility, such variability in the rate of return to human capital can induce residents of developing countries to make greater investments in education. Moreover, providing that education is relatively costly, variability in the return to human capital may increase the average level of education in a developing economy even after expected migration is netted out. Finally, our findings are shown to have explanatory power in relation to education and migratory patterns of minorities.
Keywords: F22; J15; J24; J71; O15; 330; Macroeconomic instability; Income volatility; Migration; Human capital; Ethnic discrimination; Ethnic conflicts; Minorities